DA’WAH AMONG URBAN MUSLIMS IN INDONESIA - Setiawati, Rini; Rolando, Dede Mercy; Putra, Robby Aditya; Koroglu, Osman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
The condition of da'wah portraits in the current era of information globalization which is increasingly heavy and complex is certainly a challenge for the development of da'wah. The emergence of problems that target the younger generation is a point of threat to the survival of Muslims, especially in Indonesia. This study aims to look at the portrait of the current da'wah problem and its strategy. The type of research used is a literature review. The results obtained are portraits of the problems faced and become challenges and threats for da'wah activists and da'i namely